2011
DOI: 10.1111/j.1464-0597.2011.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

What's in it for Me? Motivational Differences between Farmers' Subsidised and Non-Subsidised Conservation Practices

Abstract: Through nature conservation practices, farmers can strongly enhance nature quality and biodiversity in rural areas. In this paper, the social psychological underpinnings of farmers' nature conservation practices are investigated using the Theory of Planned Behavior, to which the concepts of self-identity and personal norms were added. A distinction is made between nature conservation practices done on a non-subsidised basis and nature conservation practices for which farmers receive some form of remuneration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 37 publications
(49 reference statements)
8
87
0
6
Order By: Relevance
“…Motivation to change behaviour (in our case, this means participating in a nature conservation governance arrangement) is closely related to a sense of ownership of nature conservation (Buizer et al, 2015;Lokhorst, Staats, van Dijk, & de Snoo, 2011). A demand for sustainable products may form an external incentive that creates a motivation to change (Mitrokostas & Apostolakis, 2013).…”
Section: Evaluating Governance Arrangementsmentioning
confidence: 99%
“…Motivation to change behaviour (in our case, this means participating in a nature conservation governance arrangement) is closely related to a sense of ownership of nature conservation (Buizer et al, 2015;Lokhorst, Staats, van Dijk, & de Snoo, 2011). A demand for sustainable products may form an external incentive that creates a motivation to change (Mitrokostas & Apostolakis, 2013).…”
Section: Evaluating Governance Arrangementsmentioning
confidence: 99%
“…We expect, however, that categorical land-use change, such as the conversion from arable farming to livestock farming or from farming to nature conservation, will arise also from land exchange from one agent type to another. This is because a categorical change often requires considerable investment in knowledge and equipment for most land owners (Rounsevell et al 2003), while it may also lead to undesired social effects such as an alienation from one's network of peers (Karali et al 2013a, b), which have been shown to strongly influence the willingness to change (Lokhorst et al 2010(Lokhorst et al , 2011. This is supported by data from the Dutch Agricultural Economics Institute, which demonstrate that-over a time span of 10 years-farms that undergo a categorical land-use change (e.g., from dairy farming to arable farming) cover about 4 % of the total agricultural area, while parcels that undergo such a change (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the vulnerability of financially dependent conservation practices are a threat to their continuity over longer time spans. Preliminary evidence for this idea was found in a study on the social psychological underpinnings of both subsidized and non-subsidized conservation (Lokhorst et al, 2011). In this study it was found that farmers' intention to engage in non-subsidized conservation was better explained by psychological aspects of their motivation than their intention to engage in subsidized conservation.…”
Section: The Instrumental Perspectivementioning
confidence: 66%